PENDAPATAN USAHATANI PARE (Momordica charanta L) DI PONDOK MANGGA KELURAHAN LOKTABAT UTARA BANJARBARU - Fitriadi, Subhan; Minta Wahyuningsih, Yayuk; Triatmoko, Eddy; Refiana, Fenny (Fakultas Pertanian UVAYA Banjarmasin, 2025)
The purpose of this research is to know technical aspects of pare farming the revenue,the eksplicit cost and the income farmer.This research was conducted in Maret until mei 2025 in pondok manga loktabat utara village. The Sensus methode used was by observing 6 farmers in village pondok mangga who planted pare plant. The Average result of the revenue is Rp. 3.960.000,/farmer, The average eksplicit cost is Rp. 565.359 /farmer, and Average income Rp. 3.394.640 /farmer.We believe that it has good prospect and revenue, of the average income ,tecnicall,economically